Sistem Nanostructured Lipid Carriers Lemak Padat Poloksamer dan Asam Stearat dengan Lemak Cair Minyak Kedelai - M Fatchur Rochman; Aditya Darmawan; Pramudya Wardhana (Jurnal Ilmiah Medicamento, 2022)
Nanostructured Lipid Carriers (NLC) are lipid-based carrier system that use a matrix combination in the form of solid and liquid which are stabilized with the addition of surfactant. This NLC was developed to facilitate the dispersion of hydrophobic bioactive compound in a hydrophilic system. This research aims to get the right formulation and can develop stable characterization, using solid lipids Poloxamer and Stearic Acid with liquid lipids Soybeans Oil using surfactant Tween 80 and co-surfactant Propyleneglycol.. The to make the formulation of NLC with a ratio of poloxamer and stearic acid as solid lipid: soybeans oil asliquid lipid is 3:3, 4:2, 5:1 ,surfactant tween 80 and co surfactant propyleneglycol. Test the NLC characterization including PH value, viscosity, particle size, and polydispersity index. Data analysis used to evaluate the characteristics of the obtained NLC using descriptive. The result of the research showed that NLC had good characteistics at a solid lipid poloxamer and stearic acid with Soybean oil liquid lipid ,pH in the range 4-6; good viscosity; good particles have a range of 1000nm; and polydispersity index which shows the results of monodispersion. Nanostructured Llipid Carriers with solid lipid poloxamer and stearic acid and liquid lipid soybean oil obtained good characteristics.